3-D geometry and irregular connectivity dictate neuronal firing in frequency domain and synchronization. (March 2019) - Ren, Tanchen; Grosshäuser, Bianka; Sridhar, Kaushik; Nieland, Thomas J.F.; Tocchio, Alessandro; Schepers, Ute; Demirci, Utkan
Abstract: The replication of the complex structure and three dimensional (3-D) interconnectivity of neurons in the brain is a great challenge. A few 3-D neuronal patterning approaches have been developed to mimic the cell distribution in the brain but none have demonstrated the relationship between 3-D neuron patterning and network connectivity. Here, we used photolithographic crosslinking to fabricate in vitro 3-D neuronal structures with distinct sizes, shapes or interconnectivities, i.e., milli-blocks, micro-stripes, separated micro-blocks and connected micro-blocks, which have spatial confinement from "Z" dimension to "XYZ" dimension. During a 4-week culture period, the 3-D neuronal system has shown high cell viability, axonal, dendritic, synaptic growth and neural network activity of cortical neurons. We further studied the calcium oscillation of neurons in different 3-D patterns and used signal processing both in Fast Fourier Transform (FFT) and time domain (TD) to model the fluorescent signal variation. We observed that the firing frequency decreased as the spatial confinement in 3-D system increased. Besides, the neuronal synchronization significantly decreased by irregularly connecting micro-blocks, indicating that network connectivity can be adjusted by changing the linking conditions of 3-D gels. Earlier works showed the importance of 3-D culture over 2-D in terms of cell growth. Here, we showed that not only 3-D geometry over 2-D culture matters, but also the spatial organization of cells in 3-D dictates the neuronal firing frequency and synchronicity.